“The Process of Institutionalization in Euro-Mediterranean Relations and Trade Exchanges in the Agrarian Sector: The Focus on Security” - Alaminos, María Ángeles (UNISCI Discussion Papers, 2014)
In this article the evolution of North South relations in the Mediterranean region is analyzed from a European perspective. It starts with the early attempts of the European Communities to negotiate trade agreements, and the first steps in the institutionalization of Mediterranean policies. In the area of trade on agricultural products it is argued that the policy formulation depends on the European political and security criteria. Food trade policy with the neighboring countries on the southern shore of the Mediterranean is not developed taken into consideration concerns related to food security and economic development in these countries. On the contrary it is subject to constraints related to European interests in security and stability, as well as the promotion of the EU normative agenda.